PENGARUH METODE GAMIFIKASI BERBASIS KAHOOT TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS VII SMP - Harefa, Yenti Warni; Buulolo, Harapan; Laia, Otinieli; Ndruru, Roswita; Gulo, Derikam; Mendrofa, Netti Kariani (Uninus Journal of Mathematics Education and Science (UJMES), 2026)
This study aimed to analyze the effect of gamification using the Kahoot platform on students’ motivation and mathematics learning outcomes in data and diagram material for seventh-grade junior high school students. The study used a quantitative approach with a quasi-experimental pretest-posttest control group design. The sample consisted of 40 students from SMP Swasta Kristen Agios Nikolaos Gunungsitoli, divided into 20 students in the experimental class and 20 students in the control class. The experimental class received mathematics learning through Kahoot-based gamification, while the control class received conventional instruction. Data were collected using pretest and posttest scores, a learning motivation questionnaire based on the ARCS model, and observation sheets. Data analysis was conducted using Shapiro-Wilk normality test, Levene’s Test, Mann-Whitney U test, and N-Gain analysis with SPSS version 24. The results showed a significant difference in posttest scores between the experimental and control classes (Sig. = 0.046 < 0.05), indicating that Kahoot-based gamification affected students’ posttest scores. However, no significant differences were found in learning motivation and N-Gain scores. These findings suggest that Kahoot is more effective in influencing final learning outcomes than directly improving students’ learning motivation.